Artikulasi Identitas Lokal Cepu dalam Novel Penangsang: Tembang Rindu Dendam Karya Nassirun Purwokartun (Tinjauan New Historicism) - Sukarjo Waluyo (SUAR BETANG, 2020)
Literature of a cultural product always interacts with social problems, including issues of locality and local identity. The problem of local identity in the novel Penangsang: Tembang Rindu Dendam is the main concern in this study. The background of the local locality and identity of Cepu which became the center of the Duchy of Jipang in the past was the setting of a place, as well as a space where the final historical and cultural journey of the power of the Demak Sultanate took place. This novel was written in 2010 by Nassirun Purwokartun. This historical novel invites us to rethink Cepu's locality and local identity, which has been a legacy of past generations. Articulation of identity and locality issues seem to be the attention voiced in this novel as well as being an instrument or instrument of articulation. This study uses the New Historicism approach, one literary theory that views history, art, and other things in society has the same degree as the text data in literature. It is hoped that literary research will get the context of the problem in accordance with the situation of the community.